A benchmarking part for evaluating and comparing support structures of additive manufacturing - Stringer, Jonathan (2018)
Additive manufacturing technology has been rapidly developed and increasingly popular nowadays; its applications spread to almost every corner in our lives. However, when printing products with overhangs, support structures are often needed, resulting in extended build time, post-processing and material waste. Numerous papers have been published on reducing support structure consumption, thus minimizing the cost and manufacture time. However, there are still no benchmarking examples and criteria in the literature for support structure comparison, resulting in hard to distinguish which method is better than another, especially in the situation that they use different standards and geometries for their research. In this paper, a specific part is proposed as a standard geometry, all research with regard to support structure can compare the results based on this benchmarking part. Line and concentric support methods from Cura 2.6.2 based on an Original Prusa i3 MK2 printer are tested and demonstrated in this paper by using this benchmarking part.